The New Eurocrats National Civil Servants in EU Policymaking - Geuijen, Karin (Amsterdam University Press, 2008)
Policies in the EU are largely made by national civil servants who prepare and implement decisions in Brussels as well as at home. Despite their important role, these national civil servants form a relatively hidden world that has received little attention from both the media and academics. This volume considers a wide variety of sources and research methods to answer such questions as: how many civil servants are actually involved in EU-related activities? What do these civil servants do when they engage with the EU? And how do they negotiate their dual roles? The New Eurocrats offers unique and invaluable insights into these civil servants and their working practices-and uncovers some secrets in the world of EU governance along the way.